PENGARUH SOCIAL MEDIA MARKETING MELALUI TIKTOK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN BRAND GLAD2GLOW DI KOTA BEKASI - Shakyla Sarah Albani; Nurul Lathifah; Dewi Rachmawati (BJRM (Bongaya Journal of Research in Management), 2026)
This study aims to analyze the influence of Social Media Marketing through TikTok and price on consumer purchase decisions for Glad2Glow products in Bekasi City. This research adopts a quantitative approach using a survey method through online questionnaires. The sampling technique employed is purposive sampling, with respondents selected based on the criteria of TikTok users who have been exposed to Glad2Glow promotional content. Data analysis is conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The results indicate that Social Media Marketing through TikTok has a positive and significant effect on purchase decisions, while price also has a positive and significant effect on purchase decisions. Simultaneously, both variables are able to explain the variation in purchase decisions within a strong category.